Sex differences in spatial abilities of medical graduates entering residency programs. Issue 6 (2nd April 2013) - Langlois, Jean; Wells, Georges A.; Lecourtois, Marc; Bergeron, Germain; Yetisir, Elizabeth; Martin, Marcel
<x xml:space="preserve">Abstract</x> Sex differences favoring males in spatial abilities have been known by cognitive psychologists for more than half a century. Spatial abilities have been related to three‐dimensional anatomy knowledge and the performance in technical skills. The issue of sex differences in spatial abilities has not been addressed formally in the medical field. The objective of this study was to test an a priori hypothesis of sex differences in spatial abilities in a group of medical graduates entering their residency programs over a five‐year period. A cohort of 214 medical graduates entering their specialist residency training programs was enrolled in a prospective study. Spatial abilities were measured with a redrawn Vandenberg and Kuse Mental Rotations Tests in two (MRTA) and three (MRTC) dimensions. Sex differences favoring males were identified in 131 (61.2%) female and 83 (38.8%) male medical graduates with the median (Q1, Q3) MRTA score [12 (8, 14) vs. 15 (12, 18), respectively; P < 0.0001] and MRTC score [7 (5, 9) vs. 9 (7, 12), respectively; P < 0.0001]. Sex differences in spatial abilities favoring males were demonstrated in the field of medical education, in a group of medical graduates entering their residency programs in a five‐year experiment. Caution should be exerted in applying our group finding to individuals because a particular female may have higher spatial abilities and a particular male may have lower spatial abilities. Anat Sci Educ 6: 368–375. © 2013 American Association of Anatomists.